Antileukemic activity and molecular docking study of a polyphenolic extract from coriander seeds - Mechchate, Hamza; de Oliveira, Regiane Costa; Es-Safi, Imane; Vasconcelos Mourão, Emmily Myrella; Bouhrim, Mohamed; Kyrylchuk, Andrii A.; Soares Pontes, Gemilson; Bousta, Dalila; Grafov, Andriy V. (Pharmaceuticals, 2021)
Leukemia is a group of hematological neoplastic disorders linked to high mortality rates worldwide, but increasing resistance has led to the therapeutic failure of conventional chemotherapy. This study aimed to evaluate in vitro the antileukemic activity and potential mechanism of action of a polyphenolic extract obtained from the seeds of Coriandrum sativum L. (CSP). A methylthia-zoletetrazolium assay was performed to assess the CSP cytotoxicity on chronic (K562) and acute (HL60) myeloid leukemia cell lines and on normal Vero cell line. CSP toxicity was also evaluated in vivo using the OECD 423 acute toxicity model on Swiss albino mice. The results demonstrated a remarkable antitumoral activity against K562 and HL60 cell lines (IC50 = 16.86 µM and 11.75 µM, respectively) although no cytotoxicity was observed for the Vero cells or mice. A silico study was performed on the following receptors that are highly implicated in the development of leukemia: ABL kinase, ABL1, BCL2, and FLT3. The molecular docking demonstrated a high affinity interaction between the principal CSP components and the receptors. Our findings demonstrated that CSP extract has remarkable antileukemic activity, which is mainly mediated by the flavonoids, catechins, and rutin, all of which showed the highest binding affinity for the targeted receptors. This study revealed a promising active compound alternative research-oriented biopharmacists to explore. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.